Identifikasi Perubahan Iklim dan Korelasinya terhadap Produksi Tanaman Padi (Oryza sativa L.) di Kabupaten Karawang - Gunawan, Gia Putra; Ruminta, Ruminta; Wicaksono, Fiky Yulianto (Paspalum: Jurnal Ilmiah Pertanian, 2024)
Rice is a food crop that is widely consumed by Indonesian people. Water availability and environmental conditions greatly influence the growth of rice plants, so that climate change can affect the production and productivity of rice plants. Efforts to anticipate a decline in rice production and productivity due to climate change require a study by identifying climate variabels, analyzing the correlation between climate and rice plants, and identifying solutions to adapt to climate change. The research was conducted in Karawang Regency using quantitative-descriptive methods, with the data analyzed being climate variabels including rainfall, temperature, humidity from 1991-2022 and rice plant variabels including rice production and productivity from 1991-2022. The analysis was carried out using trend analysis, correlation, regression, auto-regressive integrated moving average methods, and farmer interviews as analyses of adaptation strategies. The results of the research show that climate change has occurred in Karawang Regency as indicated by a decrease in rainfall intensity of 41.84 mm, a decrease in humidity percentage of 4.69%, and an increase in temperature of 〖0,92 〗^o C, and the climate type according to Oldeman is type D2, or there is no change in Oldeman’s Agroclimate zone. The results of interviews for adaptations include rotating crop planting, managing planting time, using seeds that are resistant to pest attacks, paying attention to the type of fertilizer used, controlling pests using insecticides or natural predators, and pumping water for irrigation channels.